Health Services on its way to achieving SDGS goals 3: (Good Health and Wellbeing) in East Kalimantan - Saputra, dr. Andi Satya Adi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
This study examines the progress of health services in East Kalimantan towards achieving Sustainable Development Goal 3: Good Health and Wellbeing. By analyzing relevant data and conducting interviews with key stakeholders, this research aims to identify the strengths, weaknesses, opportunities, and threats in the health system. The findings will inform the development of targeted interventions to accelerate progress towards the SDG 3 targets. This study focuses on the progress of maternal and child health services in East Kalimantan in the context of achieving Sustainable Development Goal 3. By analyzing relevant data and conducting case studies, this research aims to identify the factors that contribute to the improvement of maternal and child health outcomes, as well as the challenges that hinder progress. The findings will inform the development of evidence-based policies and programs to improve maternal and child health.